1993
DOI: 10.1113/jphysiol.1993.sp019766
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory synaptic currents in stellate cells of rat cerebellar slices.

Abstract: 1. In thin cerebellar slices of rats aged 14-21 days, voltage-gated currents, synaptic currents and GABA responses were studied with the tight-seal whole-cell recording technique from stellate cells (8-9 micrograms soma diameter) located in the outer two-thirds of the molecular layer. 2. In symmetrical Cl- conditions, stellate cells voltage-clamped at -60 mV showed spontaneous inhibitory postsynaptic currents (IPSCs). As were the GABAA responses of the same cells, the IPSCs were blocked by bicuculline. The fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
159
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(187 citation statements)
references
References 35 publications
25
159
3
Order By: Relevance
“…In addition, PC also carry extrasynaptic GABA A receptors diffusely distributed on the cell surface and are modulated by tonic inhibition, notably due to GABA release from basket cells (25). Similar, high frequency and high amplitude sIPSCs have been well characterized also in stellate cells (26,27), underscoring the major role played by postsynaptic GABA A receptors in the molecular layer.…”
Section: Organization Of Gaba a Receptors In The Cerebellar Cortexmentioning
confidence: 73%
“…In addition, PC also carry extrasynaptic GABA A receptors diffusely distributed on the cell surface and are modulated by tonic inhibition, notably due to GABA release from basket cells (25). Similar, high frequency and high amplitude sIPSCs have been well characterized also in stellate cells (26,27), underscoring the major role played by postsynaptic GABA A receptors in the molecular layer.…”
Section: Organization Of Gaba a Receptors In The Cerebellar Cortexmentioning
confidence: 73%
“…Our immunolabeling results show that a significant number of varicosities are localized close to the soma and may therefore influence the membrane potential (Vm) in the axon initial segment (AIS) substantially. This, together with the fact that MLIs have a high input resistance (Midtgaard, 1992;Llano and Gerschenfeld, 1993), made us hypothesize that single axonal synaptic events, although filtered, may strongly influence neuronal firing (as was shown previously for somatodendritic glutamatergic events; Carter and Regehr, 2002). A first indication that this is indeed the case appeared when performing the experiments in Fig.…”
Section: Activation Of Autors Increases MLI Excitabilitymentioning
confidence: 83%
“…4 D) predicts a nonfiltered (in situ) amplitude of 100 pA. In equivalent experimental conditions, Llano and Gerschenfeld (1993) reported somatodendritic GABAergic postsynaptic currents ranging between 61 and 226 pA. Assuming a singlechannel conductance of 30 pS for GABA A Rs (Bormann et al, 1987), and considering the range of values found for the autoR conductances (1-5 nS), we estimate that each presynaptic varicosity is endowed with 33-167 channels.…”
Section: Autor-mediated Synaptic Responsesmentioning
confidence: 99%
“…To study quantal release and the RRP directly, we identified individual synaptic connections and measured quantal events evoked postsynaptically by presynaptic calcium uncaging with localized laser light. Inhibitory synapses among cerebellar molecular layer interneurons (MLIs; stellate and basket cells) were used because they make only a few synaptic contacts on their postsynaptic partner and because each connection exhibits a large quantal size, on the order of 200 pA at resting potential under symmetrical Cl − conditions (3,19,20). Our strategy was to establish a recording from a synaptically connected pair of MLIs and to find the synaptic contacts between the two neurons.…”
Section: Resultsmentioning
confidence: 99%